Cho (x+y)^2 - 2(x^2+y^2) = 0 Tham khảo câu trả lời từ Trợ lý ảo Lazi Let's analyze each equation step-by-step. ### a) \((x+y)^2 - 2(x^2+y^2) = 0\) We can rewrite the equation: \[ (x+y)^2 = 2(x^2+y^2) \] Expanding the left-hand side: \[ x^2 + 2xy + y^2 = 2(x^2 + y^2) \] This simplifies to: \[ x^2 + 2xy + y^2 = 2x^2 + 2y^2 \] Rearranging gives: \[ 2xy = 2x^2 + 2y^2 - x^2 - y^2 \] \[ 2xy = x^2 + y^2 \] This can be rearranged to: \[ x^2 - 2xy + y^2 = 0 \] \[ (x - y)^2 = 0 \] Thus, this implies: \[ x = y \] ### b) \((a+b+c)^2 = 3(ab+ac+bc)\) We can expand the left-hand side: \[ a^2 + b^2 + c^2 + 2(ab + ac + bc) = 3(ab + ac + bc) \] Rearranging gives: \[ a^2 + b^2 + c^2 - ab - ac - bc = 0 \] This can be rewritten as: \[ \frac{1}{2} \left[ (a-b)^2 + (b-c)^2 + (c-a)^2 \right] = 0 \] Since all squared terms are non-negative, this indicates that: \[ a - b = 0 \quad \text{and} \quad b - c = 0 \quad \text{and} \quad c - a = 0 \] Therefore, we conclude: \[ a = b = c \] ### c) \(a+b+c=0\) Using the identity for sums of cubes, we have: \[ a^3 + b^3 + c^3 - 3abc = (a+b+c)(a^2 + b^2 + c^2 - ab - ac - bc) \] Since we know \(a + b + c = 0\), we substitute that into the equation, which results in: \[ a^3 + b^3 + c^3 - 3abc = 0 \] Thus, it simplifies to: \[ a^3 + b^3 + c^3 = 3abc \] Now, we need to verify the condition \(3abc - (a^3 + b^3 + c^3) = 0\) holds, which is fulfilled by our earlier statement. ### Conclusion: 1. \(x = y\) from part a. 2. \(a = b = c\) from part b. 3. \(a^3 + b^3 + c^3 = 3abc\) holds for \(a + b + c = 0\) in part c. Each condition establishes a relationship among the variables provided.